Effects of Uncrushed Aggregate on the Mechanical Properties of No-Fines Concrete - Memon, M. A.; Bhutto, M. A.; Lakho, N. A.; Halepoto, I. A.; Memon, A. N. (Engineering, Technology & Applied Science Research, 2018)
Concrete’s self-weight is a major aspect of a structure’s overall weight. Recently, the use of lightweight concrete (no-fines, foamed and cellular concrete) has been increased. Normally no-fines concrete is produced with crushed coarse aggregate of uniform gradation. This study aims to investigate experimentally the effects of the use of uncrushed coarse aggregates on unit weight, compressive and tensile strength of the no-fines (NFC) as well as conventional concrete (CC). In addition, the effects of coarse aggregate size on the mechanical properties were also studied. Four gradations of uncrushed coarse aggregates ranging between (5.5-4.75) mm, (10-4.75) mm, (20-4.75) mm and (25-4.75) mm were used for preparing the concretes. The fixed cement-aggregate ratios of 1:6 (with w/c ratio=0.4) and 1:2:4 (with w/c ratio=0.5) were adopted for NFC and CC respectively. It was found that the gradation of uncrushed coarse aggregate has a significant effect on the mechanical properties of NFC. A maximum of 16% reduction in self-weight of the concrete without fines was obtained, as compared to that with fines. Moreover, the compressive strength of no-fines concrete significantly improved by replacing crushed with uncrushed coarse aggregate. The compressive strength increased by 16% for the batch of (25-4.75) mm.